Colosseo. Il podio e il palco dell’imperatore.: Proposte per una ricostruzione - Beste, Heinz-Jügen; Rea, Rosella (Römische Mitteilungen, 2022)
Among the many questions still unanswered about the architectural articulation and functional modalities of some sectors of the Colosseum, the structure of the podium and of the two boxes for the highest authorities, placed frontally at both ends of the minor axis, are of particular importance. The reason for this lacuna is easily understandable: all that remains of the boxes is the empty space they originally occupied, while so little has been preserved of the podium as to make it problematic to even define its limits. On the basis of new graphic documentation and plans of the podium area made in 1812 by the architect Pietro Bianchi, who had already identified and reconstructed it graphically, a new reconstructive proposal can be made including the dimensions, extension and shape of the podium and the boxes on the minor axis.